Sustainable methods for preparing inhalation and oral solid dosage forms of nanopharmaceuticals - Yang, Yue (2015)
Nanonization is widely applied in customizing drug molecules towards drugs applicable in clinics. To fully utilize the benefits actualized from nanonization, the transformation of therapeutic nanoparticles into proper dosage forms is important. Although the commercially available dosage forms of therapeutic nanoparticles are mostly liquids, solid dosage forms are more desirable with regards to stability and convenience for patients. However, conventional techniques for preparing solid dosage forms of nanopharmaceuticals (e.g. powders for inhalation and granules, tablets or capsules for oral route of administration) are short of sustainability. Hence, this dissertation aims to develop sustainable methods for preparing controllable micron-sized agglomerates of nanopharmaceuticals as solid dosage forms for inhalation and oral routes of administration. Besides, these techniques have demonstrated their feasibility for various nanoparticles, by examinations with three types of nanopharmaceuticals including lipid-polymer hybrid nanoparticles, drug-polyelectrolyte complex, and nanocrystals. First, the feasibility of employing electrostatic adsorption of hybrid nanoparticles on charged chitosan carriers was examined and verified. The electrostatic adsorption was found to be applicable in preparing inhalation powders of lipid-polymer hybrid nanoparticles. The resultants were able to meet requirements on the physical properties for pulmonary delivery, and were also comparable to some commercial dry powder inhaler formulations with regards to single dose strength. Next, the electrostatic adsorption was applied on larger carriers to obtain granules, which can be used either as oral solid dosage forms or as raw materials for tableting or encapsulation process. Free-flowing granules of nanopharmaceuticals were obtained from the adsorption of drug-polyelectrolyte nanoplexes on neutral, positively and negatively charged crosslinked chitosan carriers. Besides, it was concluded that higher net charge of carriers would lead to higher loading of nanopharmaceuticals (either anionic or cationic) on carriers, comparing to amphibious carriers which were able to adsorb both nanopharmaceuticals. Last, a continuous granulation process by encapsulating nanocrystals in crosslinked alginate microparticles was developed instead of electrostatic adsorption to further improve the loading of nanopharmaceuticals as well as the scalability of the granulation process. As a result, the high dissolution rates of nanopharmaceuticals were kept with the developed process. The granules were fairly comparable to those from a conventional spray drying process with regards to dissolution rates. The physical properties such as tapped density and flowability were not optimized in this dissertation and recommendations for further improvements are proposed. In summary, the two methods discussed above, the electrostatic adsorption and the encapsulation, have been demonstrated as sustainable alternatives to prepare solid dosage forms of nanopharmaceuticals. While predictable microparticles could be obtained from electrostatic adsorption where the loading of nanopharmaceuticals and the physical properties are dominated by the characteristics of carriers, the encapsulation method is easier for scale-up as a continuous process and offers more flexibility in the loading of nanopharmaceuticals.